Using Virtual Reality in the Treatment of Gambling Disorder: The Development of a New Tool for Cognitive Behavior Therapy - Bouchard, Stéphane; Robillard, Geneviève; Giroux, Isabelle; Jacques, Christian; Loranger, Claudie; St-Pierre, Manon; Chrétien, Maxime; Goulet, Annie (Frontiers in Psychiatry, 2017)
Virtual reality (VR) can be used in the treatment of gambling disorder to provide emotionally charged contexts (e.g, induce cravings) where patients can practise cognitive behaviour therapy (CBT) techniques in the safety of the therapist’s office.. This raises practical questions, such as whether the cravings are sufficient to be clinically useful but also manageable enough to remain clinically safe. Pilot data is also needed to test the development of a treatment manual and prepare large randomized control trials. This paper reports on three studies describing: (a) cravings induced in VR compared to real gambling and a control game of skill with no money involved (N = 28 frequent gamblers and 36 infrequent gamblers); (b) the usefulness of a treatment protocol with only two CBT sessions using VR (N = 34 pathological gamblers); and (c) the safety of a four-session treatment program of CBT in VR (N = 25 pathological gamblers). Study 1 reveals that immersions in VR can elicit desire and a positive anticipation to gamble in frequent gamblers that are: (a) significantly stronger than for infrequent gamblers and for playing a control game of skill, and (b) as strong as for gambling on a real video lottery terminal. Study 2 documents the feasibility of integrating VR in CBT, its usefulness in identifying more high-risk situations and dysfunctional thoughts, how inducing cravings during relapse prevention exercises significantly relates to treatment outcome, and the safety of the procedure in terms of cybersickness. Results from Study 3 confirm that, compared to inducing urges to gamble in imagination, using VR does not lead to urges that are stronger, last longer or feel more out of control. Outcome data and effect sizes are reported for both randomized control pilot trials conducted in inpatient settings. Suggestions for future research are provided, including on increasing the number of VR sessions in the treatment program.